PERANAN TULANGAN TEKAN PADA BALOK TERLENTUR TULANGAN RANGKAPUNTUK MEMBANGKITKAN MOMEN NOMINAL - Puryanto Puryanto (Politeknik Negeri Sriwijaya, 2013)
Installation of compression reinforcement in the flexural beam can not be avoided . Two things which are coercive ,ie tying stirrup and high of beam restricted by the architect . Flexural beam is calculated based on the design moment . Design moment is the nominal moment multiplied by reduction factor Φ . Nominal moment is the sum of the two parts of the nominal moment . The first nominalmoment call Mn1 , ie couple between tensile force of the first tensile reinforcement NT1 = As1.fy with concrete compressive force ND = 0.85 fc '.a.b . Second nominal moment Mn2 , which is couple between the second tensile reinforcement force NT2 = As2.fy with the force of compression reinforcement ND ' = As’. Fs' . By adding compression reinforcement is expected to rise as well nominal moment . After analyzed here are four conclusions can be drawn .First , the beam does not always require compression reinforcement . Second , if the compression reinforcement is installed too deep will cause its stress decreases , it can even be ignored. Third , the compression reinforcement additional is not comparable with the nominal moment increament. The more aditonal of the compression reiforcement , the smaller the ratio of nominal moment we get. Fourth , the increase in the second nominal moment Mn 2 can continue to be done by the limit only by the availability of the place of installation.